Using Bacillus thuringiensis HM-311@hydroxyapatite@biochar beads to remediate Pb and Cd contaminated farmland soil. (November 2022) - Zuo, Wenlu; Song, Boyi; Shi, Yuxin; Zupanic, Anze; Guo, Shuxian; Huang, He; Jiang, Ling; Yu, Yadong
Abstract: Cadmium (Cd) and lead (Pb) have become serious soil contaminants in China. In this work, we immobilized B. thuringiensis HM-311 (a heavy metal resistant strain) using vinegar residue biochar and hydroxyapatite (HAP) to form Bt HM-311@HAP@biochar calcium alginate beads. In aqueous solution, the beads respectively reduced 1000 mg/L Pb 2+ to 14.59 mg/L and 200 mg/L Cd 2+ to 5.40 mg/L within 20 h. Furthermore, the results of pot experiment showed that the Bt HM-311@HAP@biochar beads reduced the bioavailability of Pb and Cd in soil. The accumulation of Pb 2+ in rice decreased by 39.97% in shoots and 46.40% in roots, while that of Cd 2+ decreased by 34.59 and 44.9%, respectively. Similarly, the accumulation of Pb 2+ in corn decreased by 40.86% in shoots and 51.34% in roots, while that of Cd 2+ decreased by 41.28 and 42.91%, respectively. The beads also increased the microbial community diversity in the rhizosphere soil. These findings indicate that Bt HM-311@HAP@biochar beads may be applicable for the bioremediation of Cd- and Pb-contaminated farmland soil. Graphical abstract: Image 1 Highlights: A heavy metal resistant BtHM-311 strain was used to form Bt HM-311@HAP@biochar beads. The beads reduced the bioavailability of Pb and Cd in soil and promoted crop growth. The beads increased the microbial community diversity in the rhizosphere soil.